The Influence Good Coorporate Governance, Banking Risks Of Banking Performance On Private Bank Foreign Exchange - Fadhly Padoli (Universitas Sulawesi Barat, 2019)
ABSTRACT This study aimed to analyze the influence of good coorporate governance, banking risks of banking performance on private bank forign exchange. The research sample was determined by the method of purposive sampling based on the criteria of private bank forign exchange are always listed on the Stock Exchange and publish financial reports are complete and present the data includes the data of the studied variables during the study period (2012-2015), in order to obtain a sample 32 bank. This study used path analysis. The results of this study concluded (1) Good Coorporate Governance have negative and significant impact on the banking risks, (2) Good Coorporate Governance have a positive and significant impact on banking performance, (3) banking risks have a negatif and significant impact on banking performance and (4) Good Coorporate Governance have a positive and significant impact on banking performance which banking risks as an intervening variable. Keywords : good corporate governance, banking risks, banking performance